Meningkatkan Hasil Belajar dan Kreativitas Siswa Melalui Penerapan Model Problem Based Learning Berdasarkan Gaya Kognitif - Ayu Dian Hijriah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
The result of Chemistry learning and creativity of students is still far from the expected standard. that is basically the background of this study. the purpose of this study is to improve student chemistry learning outcomes that have cognitive fields independent and dependent fields also student creativity on colloidal material in chemistry subject matter through the application of PBL learning model. This study is conducted in two cycles, each cycle consisting of planning, implementation, observation and reflection. In first cycle shows that student learning activities, the average learning outcomes and the frequency of students learning completeness do not reach the target yet. the results of reflection shows that there’s must be some improvements in second cycle by increasing apperception, motivation, and appreciation as well as guidance and more attention for groups of students who depend field, and the results have occurred Significant increase in: student learning activities from 67.69% to 79%. Creativity of students from 62% to 77%. The percentage of the average value of learning outcomes of independent student groups in pre-cycle 56.56, first cycle 69.13 and second cycle 81.13 with completeness frequency from 8% to 54% to 83%. And the percentage of average learning outcomes of groups of students depends on pre-cycle 43.21, cycle I 59.58 and cycle II 74.50 with completeness frequency from 0% to 33% to 67%. From the results of the study it can be concluded that the application of PBL model learning can improve student learning outcomes that have independent cognitive styles and dependent fields and can increase student creativity on colloidal material in mathematics